Attachment insecurity predicts worse outcome in patients with eating disorders treated with enhanced cognitive behavior therapy: A one‐year follow‐up study. Issue 8 (23rd June 2022) - Rossi, Eleonora; Cassioli, Emanuele; Martelli, Michela; Melani, Giulia; Hazzard, Vivienne M.; Crosby, Ross D.; Wonderlich, Stephen A.; Ricca, Valdo; Castellini, Giovanni
Abstract: Objective: This study aimed to explore the role of attachment insecurity in predicting a worse longitudinal trend of eating disorder (ED) psychopathology and body uneasiness in patients with Anorexia Nervosa (AN) or Bulimia Nervosa (BN) treated with Enhanced Cognitive Behavior Therapy, considering the longitudinal interplay between these dimensions. Method: In total, 185 patients with AN or BN performed the baseline assessment, and 123 were re‐evaluated after 1 year of treatment. Participants completed questionnaires evaluating ED psychopathology (Eating Disorders Examination Questionnaire) and body uneasiness (body uneasiness test). For the assessment of adult attachment, the Experiences in Close Relationships‐Revised was administered at baseline. Bivariate latent change score analysis within the structural equation modeling framework was performed to investigate the evolution of ED psychopathology and body uneasiness, their longitudinal interplay, and the role of attachment style as an outcome predictor. Results: After treatment, all psychopathological features showed an overall improvement. Higher baseline levels of body uneasiness predicted a worse course of ED psychopathology. The change in body uneasiness over time depended on changes over time in ED psychopathology, but not vice versa. Insecure attachment predicted a worse longitudinal trend of ED psychopathology, and, through this impairment, it indirectly maintained higher levels of body uneasiness, as confirmed by mediation analyses. Discussion: The role of attachment insecurity as a predictor of treatment outcome suggests the need for an integration of the cognitive‐behavioral conceptualization of EDs with a developmental perspective that considers attachment‐related issues. Public significance statement: Considering the burden of EDs in terms of public health and the unsatisfactory response to standard treatments, the identification of outcome predictors is of considerable clinical interest. This study demonstrated that attachment insecurity was associated with worse longitudinal trends of ED psychopathology and body uneasiness in patients with AN and BN treated with CBT‐E, highlighting the importance of personalizing treatment programs taking into account a developmental perspective on these disorders.